‘Mujeres mola’ o la máquina de imágenes míticas (2013)
This article deals with the mole as a commodity, a work of art, a ritual object and a form of visual writing -or figural, as Lyotard would say-. The first part portrays how the mola became a vestimentary object of many uses and meanings within Kuna tradition. The second part develops the artistic criteria: design, color, composition, performativity, which characterize the mole. Then, this article discusses some of the mythic and ritual dimensions that characterize the mole as an object and as a way of 'writing'. Finally, it addresses the commercial nature of the mola as a case of what Bataille calls general economy, recognizing the mole as a plane of expression that intertwines with several aspects of Kuna life. In this fusion of artistic practices, symbolic structures and practical interests highlights how the fact of 'sewing molas' has feminized Kuna culture considering the global economy of the exotic.